Kuznets Environment Curve and Sustainable Development in Vietnam - Trường, Đinh Đức; Thanh, Lê Hà (VNU Journal of Science: Social Sciences and Humanities, 2012)
Abstract . Sustainable development is one of the prime strategic orientations of most countries in the world, includingVietnam.  Apart from significant socio-economic achievements, the country’s development has been exerting considerable pressure on the environment quality inVietnam. It is therefore imperative to clearly realize and properly assess the quality of growth as well as the importance of environmental issues so as to help enhance sustainable development inVietnam. Key words: Kuznets environment curve, sustainable development, effectiveness of environmental performance.